Additional calcium carbonate into concentrate diet for sheep fed ensiled king grass as a based-diet - Mathius, I-W; Lubis, D; Wina, E; Nurhayati, D.P; Budiarsana, I.G.M (Indonesian Animal Sciences Society, 1997)
In order to ascertain the effect of additional calcium carbonate into concentrate diet, on the performance of sheep fed ensiled king grass as a basal diet, a trial was conducted using 28 growing sheep ( average body weight 17 _+ 1 .4 kg). Based on body weight, the animals were grouped and randomized into four dietary treatments in block randomized design . Dietary treatments were (i) chopped king grass + 400 g of concentrate, (ii) ensiled king grass + 400 g concentrate + 0 % of calcium carbonate, (iii) ensiled king grass + 400 g concentrate + 5 % calcium carbonate and (iv) ensiled king grass + 400 g concentrate + 10 % calcium carbonate . Results showed that offering 5 % of calcium carbonate into concentrate diet increased (P < 0 .05) dry matter and nutrient intake of silage, but digestibility coefficients were similar (P > 0 .05) for all groups . No differences in the apparent digestibility of the nutrient components were observed, but crude protein decreased significantly (P < 0 .05) . A significant relationship ( P < 0 .01) was found between nitrogen intake (NI) and nitrogen retention (NR), and the equation was Â NR = - 0.1848 + 0.3788 NI ( r = 0.9 ) . Based on data found that feeding only ensiled king grass as a single diet could not meet the maintenance requirement of energy and protein, therefore, additional energy and crude protein sources is needed . Â Keywords : Silage, king grass, growing sheep